Pop-Up Book of Profession as a Career Service Media for Elementary School Students - Bariyyah, Khairul; Hasti, Ricco Rivaldi; Susanti, Romia Hari (Universitas Nahdlatul Ulama Surabaya, 2021)
Career awareness is part of the career maturity that a child needs to achieve and needs to be provided at the primary school level. One of the media used by counselors/teachers in delivering career counseling services for elementary school children is Pop-up Book. This research is a type of development research that uses the Research and Development (R&D) technique developed by Borg and Gall until the revision stage of the test results of prospective product users. The research sample was selected using the simple random sampling technique. The research subjects were elementary school students in grade 6. The researcher involved three experts validates to assess the level, relevance, accuracy, readability, and feasibility of the media (material experts, media experts, and elementary school education experts). The instruments used were an assessment scale and a readability questionnaire for trials on elementary students. The data obtained were quantitative and qualitative data and were analyzed by manual counting using formulas. The professional pop-up book as a medium for primary school student career services developed by researchers has fulfilled relevance, accuracy, readability, and feasibility. These media are declared valid and can be used as alternative media to provide career information services for elementary school students. The results of expert testing and testing of prospective product users obtained 80.2 results with very feasible criteria to be applied and used as an alternative media for guidance and counseling services.